PENGARUH TEKNIK RELAKSASI PERNAPASAN MENGGUNAKAN AROMATERAPI TERHADAP PENURUNAN INTENSITAS NYERI PADA PASIEN POST SECTIO CAESAREA DI RB HADIJAH - Astuti Rofida; Yulia Safitri; Nurhaida Br Kaban; Nopita Yanti Str; Desi Handayani Lbs (Jurnal Kesehatan Bhakti Husada, 2026)
Background: Health promotion comprises a series of systematically designed efforts—spanning input, implementation, and outcome stages—aimed at fostering changes in health-related behavior. The success of these activities depends on various components, including delivery methods, educational materials, personnel competence, and the media employed. The synergy among these components is crucial for enhancing the effectiveness of conveying health information to the public. This study employed a pre-experimental design using a one-class pretest-posttest approach. All respondents' knowledge levels were assessed prior to receiving an intervention—specifically, health promotion regarding nutrition during pregnancy—and reassessed afterward to determine the changes that occurred. The results showed that the mean knowledge score of pregnant women was 7.34 before receiving nutrition education, rising to 10.75 after the health promotion session. The mean score increase was 3.0, with a confidence interval ranging from -lima.824 to -4.425. Analysis using a paired t-test yielded a p-value of 0.001 (p < 0.05), indicating that the nutrition-focused health promotion had a significant impact on increasing the knowledge of pregnant women at RB Khadijah. Keywords: Knowledge, Pregnant Women, Nutrition